Earth-abundant carbon catalysts for renewable generation of clean energy from sunlight and water. (November 2017) - Hu, Chuangang; Chen, Xiaoyi; Dai, Quanbin; Wang, Min; Qu, Liangti; Dai, Liming
Abstract: Water and sunlight are both renewable and readily available. A sustainable energy generation from water and sunlight holds a great promise to solve current energy and environmental challenges. However, low-cost, but efficient, catalysts are required. In this study, a rationally designed N, S co-doped three-dimensional porous graphitic network (N, S-3DPG) was used as a low-cost, highly efficient tri-functional catalyst to simultaneously catalyze hydrogen evolution reaction (HER) for photo-electrochemical water splitting to generate hydrogen fuel, oxygen evolution reaction (OER) for oxygen generation from water, and oxygen reduction reaction (ORR) for generation of clean electricity from hydrogen and oxygen gases in fuel cells. Based on the resultant multifunctional catalyst, the combination of photo-electrochemical water splitting, powered by CH3 NH3 PbI3 perovskite solar cells, for on-site generation of O2 and H2 gases with a H2 -O2 fuel cell created a cost-effective and H2 -storage-free approach toward renewable generation of clean electricity. This work represents a new conceptually important approach to cost-effective generation of clean and renewable electricity from sunlight and water. Graphical abstract: Highlights: CH3 NH3 PbX3 perovskite solar cells were used to power photo-electrochemical water splitting to generate O2 and H2 gases for fuel cells without the needs for H2 storage. Highly efficient, multifunctional ORR, OER and HER carbon catalysts were developed for integrating water-splitting with fuel cells. A novel concept for generating renewable and clean electricity from water and sunlight with zero emission of pollutants was demonstrated.